Diseño y elaboración de material didáctico en kichwa para el aprendizaje de la asignatura de Estudios Sociales en el cuarto año de educación general básica en la unidad educativa Monseñor César Antonio Mosquera - Gualsaquí Terán, Gladys Marlene (2015)
To understand the importance of developing teaching materials in Kichwa, you need to have a historical view of teaching resource, his former conception and its current approach. According Lourdes Chacha (1992) teachers teaching resources have been used for centuries, so that Pestalozzi argued that impression through the senses is the only true source of human knowledge, therefore its influence extended throughout the nineteenth and As new inventions hauled with them new technologies, the educational community received benefits in these developments because: printing, recording, photography, film, radio, television and the computer, which helped forge the collection of resources currently influencing the development of learning. But recent years have shown that bilingual schools have no teaching materials in Kichwa for any subject, which has weakened the strengthening of the mother tongue of indigenous communities. For this has been the need to design and develop teaching materials in kichwa in all areas, which will develop a teaching-learning in students, especially Social Studies, which is a subject within the school program that provides a coordinated and systematic study derives its content from discipline to help students develop the ability to make informed and reasoned decisions for the common good as full citizens in a context of cultural diversity, responding to two types of communication kichwa and castilian.